Opportunities and Barriers to Disabled Students in Higher Education: An Explorative Study of Visually Impaired Students of Aligarh Muslim University India - Abdullah; Abdul Waheed (Mediterranean Journal of Social Sciences, 2023)
The aims of the present study to investigates the opportunities and barriers that visually impaired students face in higher education at Aligarh Muslim University (A.M.U.). For this study, 20 students, including 15 (75%) males and 5 (25%) females, were interviewed based on the availability of visually impaired students. The result of this study reveals that the visually impaired students experienced three major types of barriers in the university, i.e., barriers in infrastructural accessibilities, barriers in accessing study materials, and in classroom learning. Received: 17 October 2022 / Accepted: 30 December 2022 / Published: 5 January 2023